Relationship Marketing: Association of Demography, Ethical Ideologies and Personalisation with Customer Value and Relationship Duration in Travel & Leisure Industry - Chew, Jennie Lay Peng (2010)
Casino industry relationship management has created interest among the Asia region especially with the opening of the two Integrated Resorts (IR) – Resorts World Sentosa and Marina Bay Sands in year 2010 after the success of Macau – The Asia Las Vegas. Underlying the threat to Genting Malaysia, this study is aim to analysis the relationship marketing theoretically and empirically on customer value and commitment of Genting patronage since the opening of the two IR. The dynamicity of relationship management in casino industry ponders on the relationship marketing that drives the industry to innovate in the customer relationship management. This study provides the insights on factors that influencing the success of many casinos in the region and similarity in Casino de Genting, Malaysia. This study investigates 382 patrons to Genting through questionnaire and data were analysed to determine the key dimensions. Hierarchical multiple regression analysis were conducted to examine the relationship between demography, ethical ideology, personalisation with customer value and commitment (membership tenure). The findings reveal that significant amount of variance in overall dimensions in relationship with customer value and commitment and marginal significant recorded in customer value in relationship with commitment.